2003
DOI: 10.1093/jac/dkh027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in susceptibility to posaconazole in clinical isolates of Candida albicans

Abstract: Multiple mutations in ERG11 are required to confer decreased susceptibility to posaconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 23 publications
1
64
0
2
Order By: Relevance
“…Posaconazole is known to bind more extensively to the target enzyme, 14␣-demethylase, of C. albicans than does fluconazole, due in part to the presence of a long hydrophobic side chain that serves to stabilize the binding of posaconazole to the target, making it less susceptible to the effect of point mutations in the ERG11 gene (3,50). Indeed, Li et al (17) demonstrated that isolates of C. albicans, from a patient with OPC, that were resistant to fluconazole and voriconazole but susceptible to posaconazole all had the same five missense mutations in ERG11 that specifically reduced the binding of fluconazole and voriconazole to the target enzyme. Furthermore, subsequent isolates obtained during the course of posaconazole therapy had all acquired an additional mutation, leading to the disruption of the binding of the posaconazole side chain within the hydrophobic channel of the enzyme (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Posaconazole is known to bind more extensively to the target enzyme, 14␣-demethylase, of C. albicans than does fluconazole, due in part to the presence of a long hydrophobic side chain that serves to stabilize the binding of posaconazole to the target, making it less susceptible to the effect of point mutations in the ERG11 gene (3,50). Indeed, Li et al (17) demonstrated that isolates of C. albicans, from a patient with OPC, that were resistant to fluconazole and voriconazole but susceptible to posaconazole all had the same five missense mutations in ERG11 that specifically reduced the binding of fluconazole and voriconazole to the target enzyme. Furthermore, subsequent isolates obtained during the course of posaconazole therapy had all acquired an additional mutation, leading to the disruption of the binding of the posaconazole side chain within the hydrophobic channel of the enzyme (17).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Li et al (17) demonstrated that isolates of C. albicans, from a patient with OPC, that were resistant to fluconazole and voriconazole but susceptible to posaconazole all had the same five missense mutations in ERG11 that specifically reduced the binding of fluconazole and voriconazole to the target enzyme. Furthermore, subsequent isolates obtained during the course of posaconazole therapy had all acquired an additional mutation, leading to the disruption of the binding of the posaconazole side chain within the hydrophobic channel of the enzyme (17). Thus, in order for C. albicans to exhibit resistance to posaconazole, there is a requirement for mutational events affecting the target enzyme that are over and above those necessary to produce resistance to fluconazole and voriconazole.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated strain-level discrimination for automated rep-PCR with the DiversiLab system, including mycobacteria (2) and fungi of both Aspergillus (15) and Candida spp. (3,23). The medical and economic benefit of a highly integrated, comprehensive infection control program that includes routine genotyping has been previously demonstrated (14).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of strain level differentiation, too few strains, and no strains that were clonal, were incorporated for comparison; therefore no conclusions can be drawn about its utility for strain typing fungi (8). At least two studies report the utility of the DiversiLab system for typing Candida albicans strains that have developed resistance to azoles, but the studies were not designed to compare rep-PCR to other techniques (4,10). Finally, in an analysis of both outbreak-and non-outbreak-associated Neisseria meningitidis isolates of various serogroups, the DiversiLab system had excellent serogroup and strain level discrimination (9).…”
Section: Discussionmentioning
confidence: 99%